SOMATOSTATIN RECEPTORS AS POTENTIALTHERAPEUTIC TARGETS IN THE TREATMENT OF ADVANCED ADRENOCORTICAL CANCER. A CASE REPORT - A. A. Kolomeytseva; V. V. Delektorskaya; N. F. Orel; G. S. Emelianova; V. Y. Bokhian; A. A. Fedenko (Сибирский онкологический журнал, 2018)
Background. Adrenocortical cancer (ACC) is a rare malignancy of the adrenal cortex. Therapeutic options for advanced ACC are limited. It is necessary to study new and more effective drug combinations and tumor biological targets. The purpose of the study was to determine the expression of somatostatin receptor subtypes 2A and (SSTR 2A and SSTR 5) using immunohistochemical (IHC) analysis of tumor tissue samples in patients with ACC, as well as to study the feasibility of using prolonged analogues of somatostatin in the treatment of advanced ACC. Material and methods. The expression of SSTR 2A and SSTR 5 was analyzed using imunohistochemistry of tumor tissue samples from 20 patients with advanced ACC. Results. The negative (0) IHC status of SSTR 2A and SSTR 5 was determined in 10 patients (50 %). A different staining intensity of SSTR 2A and SSTR 5 expression was found in tumor cells of 10 patients (50 %). The low SSTR expression was associated with low membrane immunoreactivity and high SSTR expression was associated with moderate and strong immunoreactivity. High level of somatostatin receptor expression was detected in 7 patients (35 %). Conclusion. The detection of SSTR 2A and SSTR 5 expression in tumor tissue of patients with advanced ACC, as well as the study of feasibility of using prolonged somatostatin analogs are promising in the treatment of patients with high receptor expression, however, further research is required.